Pengaruh Motivasi Guru dalam Meningkatkan Kedisiplinan Belajar Anak Didik di SDN I Kepuhkembeng Peterongan Jombang - Solichatun Solichatun (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
In forming discipline in students it requires motivation. So that children are more organized in carrying out learning. Therefore, the problem in this study is whether there is any influence on the motivation of teachers to improve the discipline of learning in SDN I Kepuhkembeng Peterongan Jombang. The goals to be achieved are to determine whether or not there is an influence of teacher motivation in improving student discipline in students at SDN I Kepuhkembeng Peterongan Jombang. In this study it is divided into two parts, the first part is about the study of theory, the second part about empirical studies. Theoretical study is a discussion through library studies, while empirical studies are obtained from data using the method of observation, interviews, and closed questionnaires. While the determination of the sample with a stratified proportional random sampling technique. From the data obtained, the hypothesis is tested using the Chi quadratic formula, namely:  To determine the extent of the influence of teacher motivation in improving student learning discipline in SDN I Kepuhkembeng Peterongan Jombang followed by using the Contingency Coefficient formula (KK), namely:  From the results of the study, after the data was analyzed, the conclusions were obtained that there was an effect of teacher motivation in improving students' discipline in learning at SDN I Kepuhkembeng Peterongan Jombang.